Editors' Choice—The Effect of Anchor Group and Alkyl Backbone Chain on Performance of Organic Compounds as Corrosion Inhibitors for Aluminum Investigated Using an Integrative Experimental-Modeling Approach. Issue 6 (14th April 2020) - Milošev, I.; Zimerl, D.; Carriére, Ch.; Zanna, S.; Seyeux, A.; Iskra, J.; Stavber, S.; Chiter, F.; Poberžnik, M.; Costa, D.; Kokalj, A.; Marcus, P.
Abstract : An alkaline etched, superhydrophilic aluminum surface was modified using functionalized alkyl compounds selected to study the effect of their properties on adsorption on the metal surface. The thirteen organic compounds differed in alkyl chain length (eight and eighteen carbon atoms) and anchor group (azide, imidazole, thiocyanate, amino, disulfide, thiol, phosphonic, carboxylic, and benzoic). The methodology of the study integrated a complete chain of steps incorporating synthesis, electrochemical and surface analyses, and computational modeling. The corrosion resistant and superhydrophobic properties depend on the anchor group, which governs adhesion to the surface, and backbone, which is responsible for lateral cohesive interactions. The morphology and chemical composition of modified layers were studied using scanning electron microscopy, X-ray photoelectron spectroscopy and time-of-flight secondary ion mass spectrometry. Electrochemical and long-term immersion properties were investigated in 0.5 M NaCl. Calculations based on density functional theory were performed as to model the adsorption of selected anchor groups on the hydroxylated oxidized aluminum surface. Integrated results allowed the identification of the anchor groups that are able to form inhibitive adsorbed layers on Al surface regardless the alkyl chain length, and those that are not able to form adsorbed layers at all and are thus not efficient corrosion inhibitors.